THE IMPACT OF SOCIETY ON LANGUAGE AND LINGUISTICS - Sabirova Nafisa Qurolbayevna (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This study explores the dynamic relationship between society and language, emphasizing the influence of social factors such as class, gender, ethnicity, and power dynamics on linguistic practices. The article investigates how language reflects social identity, group membership, and broader societal values. It draws on sociolinguistic theories and frameworks such as Social Identity Theory, Speech Act Theory, Sociolinguistic Variation, and Critical Discourse Analysis to demonstrate how language both shapes and is shaped by the society in which it operates. The study underscores the role of language in social stratification, cultural preservation, and social movements, offering valuable insights into the complex ways language functions as a social tool. Through a comprehensive analysis, the research highlights language as a powerful medium for understanding and challenging societal norms.